The Influence Of Member Participation On Resulting Business Results In Mandiri Credit Union Cooperatives - Elpita R. Nababan; Susy A. Sibagariang; Binsar Tison Gultom (CV Putra Publisher, 2023)
This study aims to determine the effect of member participation on the remaining business results of the Mandiri Credit Union Cooperative. This research was conducted at the Mandiri Credit Union Cooperative, Pandiangan Village. The population in this study were 41 members and the samples were taken from the principal savings report, mandatory savings voluntary savings and the remaining results of operations for 36 months. Data collection techniques use documentation by collecting financial report data at the Mandiri Credit Union cooperative. The analytical method used in this study is multiple linear regression analysis using the Ordinary Least Square (OLS) method using SPSS 25.0 software for Windows. The results of testing the hypothesis have proven that principal savings have a positive and significant effect on the remaining operating results because tcount 6.257 > table 1.687, mandatory savings have a positive and significant effect on the remaining operating results because tcount 1.973 > ttable 1.687, voluntary have a positive and significant effect on the remaining operating results because tcount 3.426 > ttable 1.687 and the significant level of variables X1 (0.000 > 0.05), X2 (0.056 savings > 0.05), X3 (0.002 > 0.05)